MICROPLASTIC REMOVAL IN SEAWATER SALT PONDS THROUGH MF/UF MULTI-STAGE MEMBRANE FILTRATION - Putra Pradana, Hilmi
The sea serves as a dumping ground for waste from various sources, leading to contamination by microplastics that can permeate into seawater. This contaminated seawater is used as raw material for salt production, thus transporting microplastics into the salt. The presence of microplastics in salt, an essential universal seasoning commodity, poses a risk of ingestion and health issues due to the chemicals in microplastics and their ability to adsorb Persistent Organic Pollutants (POPs) like those causing cancer and nerve damage. Filtration is a suitable alternative to be applied in the salt production process to reduce microplastics in the resulting salt. This study aims to determine the correlation between the abundance of microplastics in seawater and salt from three salt-producing regions in Central Java; to assess the difference in microplastic removal efficiency based on abundance in brine samples using single-stage and multi-stage filtration; and to investigate the effect of pressure variation on flux (J), transmembrane pressure (TMP), and removal efficiency in a multi-stage membrane filtration configuration. The membrane filters used in this study consist of polypropylene (PP) microfiltration membranes with a pore size of 1 µm and polyvinylidene fluoride (PVDF) ultrafiltration membranes with a pore size of 0.01 µm, which are commonly found in the Indonesian market for ease of application of research results. This study comprises three stages. The first stage includes the extraction and identification of microplastics in salt and seawater samples from three salt-producing regions, as well as the creation of artificial microplastics through cryogenic milling adjusted to the region with the highest abundance. The second stage involves the setup and adjustment of filtration reactor parameters during the pre-research phase. The final stage involves the filtration process based on variations in single-stage and multistage membrane configurations and pressure variations in ultrafiltration with artificial microplastics, with an increase in abundance by 1.5 times the highest abundance to determine the optimal removal rate variation. The optimal variation results are used for experiments with seawater solution from the region's salt with the highest abundance. Each variation includes membrane replacement and backwash on the ultrafiltration membrane for each replication of the variation. From the three salt-producing regions in Central Java, namely Rembang, Pati, and Jepara, the abundance of microplastics in salt samples ranges from 610 to 1400 MPs/kg, with Rembang being the region with the highest abundance. Meanwhile, the abundance of microplastics in seawater ranges from 51.5 to 107 MPs/L. The correlation coefficient (r) between the abundance of microplastics in salt and seawater is 0.8109, indicating a strong positive correlation, with a determination coefficient (r²) of 65.8%. Identified microplastics predominantly have shapes such as lines/fibers/filaments and films/sheets, dominant sizes of 100–500 µm and 750–1000 µm, dominant colors of black and colored, and PET as dominant polymer. Filtration results with artificial microplastics predominantly sized 50–150 µm through variations in membrane configurations and pressure show the highest microplastic removal efficiency in multi-stage filtration with 3 bar pressure on the microfiltration membrane and 3.5 bar pressure on the ultrafiltration membrane, achieving up to 89.4%. Pressure variations in membrane filtration affect the increase in flux values and TMP, but do not influence the increase in removal efficiency. The microplastic removal efficiency in artificial seawater from Rembang salt ranges from 87.23% to 90% in the optimal variation. Based on this study, removal efficiency is influenced by the characteristics of the filter membrane and microplastics.